You are on page 1of 12

GIKPKC7 94107 Trigonometry Page 1

Introduction
3/6/98
Trigonometric Ratios:
O (90  )
Sine sin  
H
A O = Opposite H = Hypotenuse
Cosine cos  
H
O Hint: 
Tangent tan   A = Adjacent
A ‘O’ on top, ‘H’ below,
‘A’ where it fits.

Inverse Ratios:
1 H
Cosecant cos ec  
sin  O
1 H
Secant sec   
cos  A
1 A
Cotangent cot   
tan  O

Complementary Angles:
A
sin 90   

H
O
cos 90    
H
A
tan 90   
O
H
cos ec90    
A
H
sec90    
O
A
cot 90   

O

Results from Complementary Angles and Inverse Ratios:


sin  = cos (90  )
cos  = sin (90  )
tan  = cot (90  )
cosec  = sec (90  )
cot  = tan (90  )
sec  = cosec (90  )
Luke Cole Page 1
GIKPKC7 94107 Trigonometry Page 2

Exact Ratios:

Hint: 0 30 45 60 90


1
2
=
0.707

3
2
sin 0 1 1 3 1
2 2 2
cos 1 3 1 1 0
2 2 2
tan 0 1 1 3 E
3

Angle of Depression & Elevation:


1 1 = Depression
2 = Elevation
2 1 = 2

Bearings:
Compass N
A  N 50 E
50 A
B  S 65 W
W E
25

B
S
N

50 A

W E
25

B
Luke
S Cole Page 2
GIKPKC7 94107 Trigonometry Page 3

True North
N 0
A  50
B  245
50 A

270 90
25

B
180

Angles of Any Magnitude:


y 90
2nd Quadrant 1st Quadrant
S A
(sin +ve) (All +ve) x Hint:
180 0 All Stations
T C Too Central
(tan +ve) (cos +ve)
3rd Quadrant 4th Quadrant

270
Proof:
Construct a unit circle [r = 1, c(0, 0)]:
1st Quadrant 2nd Quadrant
y y
P(x, y) P(x, y)

 x x 
y y
sin 180    

sin   y y
1 1
x x
cos 180    

cos    x  x
1 1
y y
tan   tan 180    
x x
 All +ve  sin +ve

Luke Cole Page 3


GIKPKC7 94107 Trigonometry Page 4

3rd Quadrant 4th Quadrant

x   x

P(x, y) P(x, y)
y y
y y
sin 180      y sin 360     y
1 1
x x
cos 180    cos 360      x
 
 x
1 1
y y y
tan 180     tan 360   
 

x x x
 tan +ve  cos +ve
Trigonometric Identities
10/6/98
From the Unit Circle:

¼ of it:

1 y

sin 
Equation: tan  
cos 
Proof:
From unit circle:
sin  = y …(1)
cos  = x …(2)
y
tan   …(3)
x
Sub (1) & (2) into (3):
sin 
 tan  
cos 

Equation: sin2  + cos2  = 1


Proof:
Using Pythagoras:
x2 + y2 = 12

Luke Cole Page 4


GIKPKC7 94107 Trigonometry Page 5

 sin2  + cos2  = 1 …[1]

Equation: cosec2   cot2  = 1


Proof:
Divide [1] by sin2 :
sin 2  cos 2  1
 
sin  sin  sin 2 
2 2

 cosec2   cot2  = 1

Equation: sec2   tan2  = 1


Proof:
Divide [1] by cos2 :
sin 2  cos 2  1
 
cos  cos  cos 2 
2 2

 sec2   tan2  = 1
Sine Rule:
sin A sin B
Equation: 
a b
Proof:
h
Here, sin B 
c
h = c.sin B …(1) A
h
sin C 
b c h b
h = b.sin C …(2)
So, (1) = (2):
c.sin B = b.sin C B a C
sin B sin C
 
b c

Cosine Rule:
b2  c 2  a 2
Equation: a2 = b2 +c2 – 2.b.c.cosA or cos A 
2.b .c
Proof:

Luke Cole Page 5


GIKPKC7 94107 Trigonometry Page 6

In ACD, x2 + p2 = b2 C
In BCD, (c – x)2 + p2 = a2
c2 – 2.c.x + b2 = a2
x b p a
In ACD, cos A 
b
x = b.cosA
So, a2 = b2 + c2 – 2.b.c.cosA A x D c x B
c
Area of a Triangle Rule:
Equation: A = ½.a.b.sinC
Proof:
Since, A = ½.b.h B
h
And, sin C 
a a h c
h = a.sin C
 A = ½.b.a.sin C
C b A

More Special Results:


Equation: cos (x – y) = cos x.cos y + sin x.sin y
Proof:
From the unit circle:

P Q

y
 
A x O x B

At point Q(x, y): At point P( x, y):


(1) cos  = x (1) cos(180  ) =  x
(2) sin  = y  cos  =  x
 Q(cos , sin ) cos  = x
(2) sin (180  ) = y
sin  = y
 P(cos , sin )
Now, using the distance formula:
PQ2 = (cos   cos )2 + (sin   sin )2
PQ2 = cos2   2.cos  .cos  + cos2  + sin2   2.sin  .sin  + sin2 
Luke Cole Page 6
GIKPKC7 94107 Trigonometry Page 7

PQ2 = 2 – 2(cos  .cos  + sin  .sin ) …(1)


Using the cos Rule:
PQ2 = 12 + 12 – 2.1.1.cos (  )
PQ2 = 2 – 2.cos (  ) …(2)
So, (1) = (2):
2 – 2(cos  .cos  + sin  .sin ) = 2 – 2.cos (  )
 cos (  ) = cos  .cos  + sin  .sin 
Now let  = x &  = y:
cos (x – y) = cos x.cos y + sin x.sin y …[1]

Equation: cos (x + y) = cos x.cos y  sin x.sin y


Proof:
From [1] let y =  y:
cos [x – ( y)] = cos x.cos ( y) + sin x.sin ( y)
 cos (x + y) = cos x.cos y  sin x.sin y

Equation: sin (x + y) = sin x.cos y + cos x.sin y


Proof:
From [1] let x = 90 – x:
cos [(90 – x) – y] = cos (90 – x).cos y + sin (90 – x).sin y
cos [90 – (x + y)] = sin x.cos y + cos x.sin y
 sin (x + y) = sin x.cos y + cos x.sin y …[2]

Equation: sin (x – y) = sin x.cos y – cos x.sin y


Proof:
From [2] let y =  y:
sin [x + ( y)] = sin x.cos ( y) + cos x. sin ( y)
 sin (x – y) = sin x.cos y – cos x.sin y

tan x  tan y
Equation: tan  x  y  
1  tan x . tan y
Proof:
Since:
sin x  y 
tan x  y  
cos  x  y 
sin x. cos y  cos x . sin y
=
cos x .cos y  sin x . sin y
Divide by cos x. cos y:
Luke Cole Page 7
GIKPKC7 94107 Trigonometry Page 8

sin x .cos y  cos x. sin y


cos x .cos y
tan x  y  
cos x .cos y  sin x . sin y
cos x .cos y
tan x  tan y
 tan x  y   …[3]
1  tan x. tan y

tan x  tan y
Equation: tan  x  y  
1  tan x . tan y
Proof:
From [3] let y =  y:
tan x  tan y 
tanx   y  
1  tan x .tan  y 
tan x  tan y
 tan x  y  
1  tan x. tan y

Ratios of Double Angles:


Equation: sin (2.x) = 2.sin x.cos x
Proof:
Since, sin (x + y) = sin x.cos y + cos x.sin y
sin (x + x) = sin x.cos x + cos x.sin x
= 2.sin x.cos x
 sin (2.x) = 2.sin x.cos x

Equation: cos (2.x) = cos2 x  sin2 x


= 2.cos2 x  1
= 1 – 2.sin2 x
Proof:
Since, cos (x + y) = cos x.cos y  sin x.sin y
cos (x + x) = cos x.cos x  sin x.sin x
= cos2 x  sin2 x
 cos (2.x) = cos2 x  sin2 x

2. tan x
Formula: tan 2.x  
1  tan 2 x
Proof:
tan x  tan y
Since, tan x  y  
1  tan x. tan y
Luke Cole Page 8
GIKPKC7 94107 Trigonometry Page 9

tan x  tan x
tan x  x  
1  tan x. tan x
2.tan x
=
1  tan 2 x
2.tan x
 tan 2.x  
1  tan 2 x

Ratios in Terms of “T Results”:


2.t x
Equation: sin x  2 where, t  tan
1 t 2

Proof:
Since, sin (2.x) = 2.sin x.cos x
x x t2  1
sin x  2. sin .cos t
2 2
t 1
= 2. 2 . x
t 1 t 1
2 1
2
2.t
 sin x 
1 t2

1t2 x
Equation: cos x  2
where, t  tan
1t 2
Proof:
Still working with the above triangle
Since, cos (2.x) = cos2 x  sin2 x
x x
cos x  cos 2  sin 2
2 2

Luke Cole Page 9


GIKPKC7 94107 Trigonometry Page 10

2 2
 1   t  Note: T-results will always
cos x      solve any trigonometry
2   2 
 t  1   t  1  equations except when  = 180
1 t2 (Since, tan 90 = Err)
= 
t2 1 t2  1
1 t2
 cos x 
1 t2

2.t x
Equation: tan x  where, t  tan
1 t2 2
Proof:
2.tan x
Since, tan 2.x  
1  tan 2 x
x
2.tan
tan x  2
x
1  tan 2
2
2.t
 tan x 
1 t2

General Solutions
31/7/98
Equation: sin  = sin  is  = 180  n + ( 1)n  
n = Integer
Proof by e.g.:
3
Find all the solutions for sin   , here the domain is not restricted.
2

 = 60, 120,……
+
 = 60, (180 – 60), (360 + 60), (540 – 60), …
 can also be negative

 = – (180 + 60), – (360 – 60), – [360 – (180 – 60)], …
= (– 180 – 60), (– 360 + 60), (– 540 – 60), …
 The general solution for sin  = sin 60 is:
 = 180  n + (– 1)n  60

Equation: cos  = cos  is  = 360  n  


n = Integer

Equation: tan  = tan  is  = 180  n + 


n = Integer

Luke Cole Page 10


GIKPKC7 94107 Trigonometry Page 11

Note: These above equations are for


+ve angles, change the equation to
suite you need if the angle is –ve.

Trigonometry Graphs
16/9/98
y = sin x:
1

1

Period: T = 2. rad


Amplitude: yA = 1 unit

y = cos x:

Luke Cole Page 11


GIKPKC7 94107 Trigonometry Page 12

1
Period: T = 2. rad
Amplitude: yA = 1 unit

y = tan x:
1

1

Period: T =  rad

Asymptote: x  rad
2

Luke Cole Page 12